The Nexus Between Academic Culture and Collaborative Culture as an Academic Collaborative Culture for Effective Teaching in Higher Education - Otto Berman Sihite; Sinaga Poltak; Dylmoon Hidayat; Rosdiana Sijabat (Universitas Negeri Malang, 2022)
It becomes a challenge for lecturers to provide services to the community through a culture of collaboration that makes it easier for academics to make their contribution to society. This study aims to investigate the relationship between academic culture and collaborative culture as a collaborative academic culture for effective teaching in higher education. This study involved 35 lecturers as respondents in this survey from five universities in Indonesia. A Likert scale was used to collect data from an online survey using Google Forms, and Smart-PLS was applied to evaluate the data. The findings of the study indicate that this climate must be cultivated so that a culture of academic collaborative is achieved optimally. The two concepts are understood implicitly but remain a unity and an interaction that is not confusing in implementation to study the dynamics of institutional behavior and encourage or manage effective teaching improvement. Keywords: Academic collaborative culture, effective teaching, academic culture